Curcumol repressed cell proliferation and angiogenesis via SP1/mir-125b-5p/VEGFA axis in non-small cell lung cancer - Ma, Changju; Tang, Xiaojuan; Tang, Qing; Wang, Shiyan; Zhang, Junhong; Lu, Yue; Wu, Jingjing; Han, Ling (Frontiers in Pharmacology, 2022)
NSCLC (non-small cell lung cancer) is one of the most common and lethal malignant tumors, with low 5-year overall survival rate. Curcumol showed antitumor activity in several cancers, but evidence about its effect on NSCLC remains unclear. In the present study, we found that Curcumol markedly inhibited NSCLC cells proliferation, migration and invasion. Endothelial cells are an important part of tumor microenvironment. Tube formation assay and wound healing assay indicated that A549 derived conditioned medium affected HUVECs (human umbilical vein endothelial cells). Mechanistically, Curcumol downregulated the expression of SP1 (specificity protein 1) while upregulated miR-125b-5p, followed by decreasing VEGFA expression in NSCLC cells. Furthermore, overexpression of SP1 partially reversed the inhibitory effect of Curcumol on A549 and H1975 cell viability and VEGFA expression. Inhibition of miR-125b-5p presented similar effect. Interestingly, there was mutual modulation between SP1 and miR-125b-5p. Collectively, our study revealed that Curcumol inhibited cell growth and angiogenesis of NSCLC in vitro and in vivo, possibly through SP1/miR-125b-5p/VEGFA regulatory mechanism. These findings may provide effective therapy strategies for NSCLC treatment.